Kepemimpinan Perempuan Dalam Al-Quran : Studi Komparasi Tafsir Al-Azhar Dan Tafsir An-Nur - Mizan, Muhammad; Arif Firdausi N.R; Muhammad Mukharom Ridho (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
This study discusses women's leadership in the Qur'an. Where the issue of women's leadership is a topic that is always interesting, even seems to be a prolonged polemic, both from men and women themselves, intellectuals and laity. It is also a controversial issue among contemporary scholars, each arguing for whether or not women should be leaders. This research uses Abdul Mustzim's theory, which is the muqarran (comparison) method between Buya Hamka in Al-Azhar and Hasbi Ash-Shiddiqye in An-Nur. The leadership of men over women in the household must not be authoritarian.